Effects of silybin on triptorelin-induced bone metabolic abnormalities in prostate cancer revealed based on TMT-based proteomics - Jianhui Li; Xuejiao Lv; Ying Jiang (PLoS ONE, 2026)
Aims The aim of this study was to investigate the mechanism of action of SB on TRP-induced abnormalities of bone metabolism in LNCaP cells. Methods The effects of different concentrations of SB and TRP alone and in combination on the proliferation of LNCaP cells were examined by CCK-8 assay, and the half maximal inhibitory concentration were screened for the subsequent experiments. Transwell migration and invasion assays were used to further investigate the effects of SB and TRP alone and in combination on the migration and invasion ability of LNCaP cells. Based on Tandem Mass Tag (TMT) labeling and liquid chromatography-tandem mass spectrometry (LC-MS/MS) technology, the differentially expressed proteins (DEPs) of LNCaP cells in the control group, SB group, TRP group and combination group were quantified. Bioinformatics technology was used to analyze the DEPs of LNCaP cells in each group. At last, the achieved key targets were verified by western blot. Results The inhibitory effects of different concentrations of SB and TRP alone and in combination on the proliferation, migration and invasion of LNCaP cells showed both time-dependent and concentration-dependent effects, and the inhibitory effects of the combination of drugs on LNCaP cells were more significant. The proteomics results showed that a total of 153 DEPs were identified in the SB group and the control group, 100 DEPs were identified in the TRP group and the control group, and 524 DEPs were identified in the combination group and the control group. Bioinformatics analysis showed that a higher number of DEPs were enriched in the IL-17 signaling pathway in the SB and combined treatment groups compared to the control group. These findings suggest a potential role of SB and the combined treatment in modulating the IL-17 signaling pathway. In contrast, the same DEPs were found to be enriched in both the Circadian entrainment and Apelin signaling pathways in the TRP versus control and combined treatment versus control comparisons. Conclusions SB may regulate TRP-induced bone metabolism abnormalities in LNCaP cells through the IL-17 signaling pathway as well as five DEPs: p-ERK2, RELA, HSP90B1, GNAI1and GNAI3.